Role of contrast-enhanced magnetic resonance high-resolution variable flip angle turbo-spin-echo (T1 SPACE) technique in diagnosis of transverse sinus stenosis. Issue 120 (November 2019) - Quan, Tao; Ren, Yanan; Lin, Yanan; Guan, Sheng; Hou, Haiman; Yan, Baojun; Cheng, Jingliang; Xu, Haowen
Highlights: Contrast-enhanced T1 SPACE was highly accordant with DSA in measuring TSS. Intermodality agreement was better for enhanced T1 SPACE than for PC MRV compared with DSA. Small filling defects could be found on enhanced T1 SPACE sequence. Abstract: Purpose: Transverse sinus stenosis (TSS) is the most sensitive imaging characteristic of idiopathic intracranial hypertension (IIH). This study aimed to assess the diagnostic performance of contrast-enhanced magnetic resonance high-resolution variable flip angle turbo-spin-echo (T1 SPACE) technique in TSS patients and evaluate the diagnostic accuracy of enhanced T1 SPACE, and phase-contrast magnetic resonance venography (PC MRV) with digital subtraction angiography (DSA) as standard imaging. Method: This prospective study enrolled 62 patients with suspected IIH and PC MRV-confirmed transverse sinus stenosis. All patients underwent lumbar puncture, PC MRV, enhanced T1 SPACE sequences and DSA examination. The accuracy, sensitivity, and specificity of enhanced T1 SPACE in detecting venous sinus stenosis were calculated and compared with those of PC MRV. Intermodality agreement (Kendall's rank correlation coefficients and weighted kappa statistic) was assessed. Results: Sixty-two patients were enrolled from November 2016 to October 2018. For the measured stenosis, better correlation was observed in enhanced T1 SPACE and DSA (AUC = 0.953) than PC MRV (AUC = 0.871). Intermodality agreement of enhanced T1 SPACE (rk  = 0.895 and weighted ĸ = 0.868) was better than PC MRV (rk  = 0.753 and weighted ĸ = 0.653) compared with DSA. Thirty-seven intrasinus filling defects were detected by contrast-enhanced T1 SPACE, while only twenty of them were detected on source imaging of PC MRV. Conclusions: The contrast-enhanced T1 SPACE sequence was more sensitive and specific compared with PC MRV in assessing stenosis and detecting lesions in TSS patients. Accurate determination of the presence and extent of TSS using this technique might be useful in patient selection and guiding the treatment.